The Swarm Initial Field Model for the 2014 geomagnetic field. Issue 4 (25th February 2015) - Olsen, Nils; Hulot, Gauthier; Lesur, Vincent; Finlay, Christopher C.; Beggan, Ciaran; Chulliat, Arnaud; Sabaka, Terence J.; Floberghagen, Rune; Friis‐Christensen, Eigil; Haagmans, Roger; Kotsiaros, Stavros; Lühr, Hermann; et al.
Abstract Data from the first year of ESA's Swarm constellation mission are used to derive the Swarm Initial Field Model (SIFM), a new model of the Earth's magnetic field and its time variation. In addition to the conventional magnetic field observations provided by each of the three Swarm satellites, explicit advantage is taken of the constellation aspect by including east‐west magnetic intensity gradient information from the lower satellite pair. Along‐track differences in magnetic intensity provide further information concerning the north‐south gradient. The SIFM static field shows excellent agreement (up to at least degree 60) with recent field models derived from CHAMP data, providing an initial validation of the quality of the Swarm magnetic measurements. Use of gradient data improves the determination of both the static field and its secular variation, with the mean misfit for east‐west intensity differences between the lower satellite pair being only 0.12 nT.